2020
DOI: 10.3389/fnut.2020.00110
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Concentrations in Human Milk Are Associated With Infant Weight and BMI From Birth to 5 Years

Abstract: Background: Human milk bioactives may play a role in infant health and development. Although the variability in their concentrations in milk is well-established, the impact of differential milk profiles on infant growth outcomes remains unclear. Thus, the aim of the present study was to investigate whether different concentrations of metabolic hormones are associated with different weight and BMI in infants beyond the first year of life. Methods: Milk samples at 2.6 (±0.4) months after birth and anthropometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 64 publications
2
21
0
1
Order By: Relevance
“…The results confirmed our hypothesis that variability in MOM hormonal composition may contribute to variation in postnatal growth and that infants of different sex are likely to respond differently to the same concentrations of MOM components. Importantly, the data also confirm our previous observations in the healthy Finnish STEPS cohort regarding the correlations between MOM IGF-1 concentrations and infant weight (18), highlighting the possibility that exposure to varied MOM IGF-1 concentrations is associated with variation in infant growth outcomes (e.g., weight, BMI, body composition). We observed fat-free mass at discharge from hospital and at 4 months' corrected age was lower for infants whose mothers had a higher MOM protein content during early lactation (day 5 postpartum).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results confirmed our hypothesis that variability in MOM hormonal composition may contribute to variation in postnatal growth and that infants of different sex are likely to respond differently to the same concentrations of MOM components. Importantly, the data also confirm our previous observations in the healthy Finnish STEPS cohort regarding the correlations between MOM IGF-1 concentrations and infant weight (18), highlighting the possibility that exposure to varied MOM IGF-1 concentrations is associated with variation in infant growth outcomes (e.g., weight, BMI, body composition). We observed fat-free mass at discharge from hospital and at 4 months' corrected age was lower for infants whose mothers had a higher MOM protein content during early lactation (day 5 postpartum).…”
Section: Discussionsupporting
confidence: 87%
“…Such metabolic hormones contained in HM (i.e., leptin, adiponectin, and growth factors) regulate multiple biological functions (14) and are potential mediators of infant health outcomes across the life course by providing important environmental cues at critical time-points of developmental plasticity (15)(16)(17). In this context, our study in a healthy Finnish cohort has recently demonstrated that growth trajectories up to 5 years were associated with HM concentrations of insulin-like growth factor (IGF)-1 (18). Similarly, others have reported associations between HM composition and diverse infant growth trajectories (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 93%
“…IGF1 is found in human milk, in a bioactive form in the intestine of breastfed infants and in their blood serum at higher concentrations [ 195 ]. Very recent research links its concentration in human milk with an important role in defining infant growth trajectories beyond the first year of life [ 230 ] and supports previous studies that highlighted its importance in infant growth and regulation of fat accumulation during childhood [ 231 ].…”
Section: Growth Factors (Gfs)supporting
confidence: 60%
“…Such predicted associations between maternal BMI and milk metabolic hormones, based on the strong and consistent association between body composition and leptin, are frequently reported even in the absence of such data (Andreas et al, 2016;Chan et al, 2018;Galante et al, 2020;Martin et al, 2006;Quinn et al, 2015;Sims et al, 2020;Young et al, 2017). Such interpretations act to obscure important, small biological differences in milk composition that may have important long term programming effects on infant metabolic phenotype (Fewtrell et al, 2020;Kuzawa & Quinn, 2009).…”
Section: Aim #3: Review the Evidence Showing How Using Maternal Bmimentioning
confidence: 98%